Optimization of oxidation desulphurization of power-generating coal - Pysh’yev, Serhiy; Bilushchak, Halyna; Gunka, Volodymyr (Publishing House of Lviv Polytechnic National University, 2012)
An experimental statistic model of powergenerating coal oxidative desulphurization has been developed and its adequacy has been proved. On the basis of the proposed model the desulphurization optimal conditions for three samples of power-generating coal were determined. The low-sulphur solid fuel with the content of general sulphur of 1.0–1.5 mas % was obtained under established optimal conditions. Створено експериментально-статистичну модель процесу оксидаційного знесірчування кам'яного енергетичного вугілля та доведено її адекватність. З використанням запропонованої моделі знайдено оптимальні умови проведення знесірчування трьох зразків кам'яного енергетичного вугілля. Проведення процесу за цих оптимальних умов дозволило отримати низькосірчисте тверде паливо (вміст загальної сірки не перевищував 1.0-1.5% мас.).
Оптимізація процесу оксидаційного знесірчування кам’яного енергетичного вугілля
Keywords: oxidative desulphurization; coal; sulphur; pyrite; modeling; оксидаційне знесірчування; вугілля; сірка; пірит; моделювання